Performance Evaluation of a Triple Layer Electric Sieving Machine (TLESM) - Adedipe J.O; Aderemi A.M; Oyewole O.O; Abegunrin, O.O; Olatunji B.T; Afolabi R.T (International Journal of Engineering and Management Research, 2021)
A multi-layer sieving machine is of multiplayer and highly efficient sieving machine that retains particles based on the difference in size. This study was carried out to evaluate the performance of a multi-layer electric sieving machine. The performance test of the machine was carried out in the Agricultural department farm of the Federal College of Forestry, Jericho Ibadan. The electrical sieving machine was used to carry out separation operations on a mixture of food crop materials at varying speeds. The machine passed the test of workability; it was able to perform the specific function of sieving and separating food materials of varying sizes. Mixed food materials were poured in the first layer of the mesh assembly and sieved. The time to completely separate the mixture into the three different layers was recorded and the respective weight of each layer was finally measured. Layer 1 had a mean weight gain of 0.42kg; layer 2 had a mean weight gain of 0.14 while layer 3 had a mean weight loss of 0.56kg when sieving was done for 5 minutes; at 7 minutes, Layer 1 had a mean weight gain of 0.1kg; layer 2 had a mean weight gain of 0.18 while layer 3 had a mean weight loss of 0.28kg, while at 10 minutes, the first layer had a mean weight gain of 0.06 kg, second layer also had mean weight gain of 0.02 while the third layer had a mean weight loss 0.08. The mean efficiency was highest at 99% in all the layers when sieving operation was carried out for 10 minutes and lowest at 96% for layer 3 when the machine ran for five (5) minutes. The effect of change in speed suggests that increment in sieving speed above 750rpm or below 300rpm gives a low efficiency.